PERHITUNGAN PELAT CENDAWAN BETON BERTULANG DENGAN METODE PERENCANAAN LANGSUNG DAN METODE PORTAL EKIVALEN PADA PROYEK PEMBANGUNAN GEDUNG DISPERINDAG KOTA SAMARINDA - RAPA, BERTOMILIUS (KURVA S JURNAL MAHASISWA, 2013)
Flat slab is replaced with plate system the principle function of the beam along the lines of columns with plates floors, while the edges of the beam to be held steady. Flat slab has sufficient shear strength with drop panels or the head of a column or both. The purpose of this planning is to know the result of the system of the flat slab with equivalent portal methods as well as the volume of the concrete needs of the actual conditions of the plates with the bars. At this writing, the flat slab is planned by using the methods have corresponding portals. This method is the fact that the approach of the framework the framework of three dimensional portal into a two-dimensional portal frame in the field column. This approach requires the system of relationships between columns with columns of flexural strength of plates i.e. the transfer of the license plate to the tip of its components meet fields. The results of this planning is a flat slab: thickness of plates or plate dimension (15 cm); thick drop panel to floor plates (4 cm); the length of the column axis drop panels to the outer side of the drop panels (150 cm); the volume of concrete needs more economical than plain beams with plates. On the planning of this flat slab, which is obtained in terms of artistic merit seem nicer, and easily arranged as needed on a settlement.